Pengaruh Kepemimpinan, Kepuasan Kerja dan Komitmen Organisasional terhadap Organizational Citizenship Behavior (OCB) Perawat RSD Panembahan Senopati Bantul - R. Jati Nurcahyo (Universitas Islam Indonesia, 2012)
This research resulted as the following (1) to examine the influence of leadership on Organizational Citizenship Behavior (OCB). This was proved that t statistics (t test) was obtained, got t-statistic 6,088 and error level probability (p-value) by 0,000; (2) to examine the influence of leadership on organizational partnership. This was proved in the coefficient significance test which resulted got t-statistic -1,265 and p-value 0,208, (3) to examine the influence of leadership on working satisfaction. This was proved in the coefficient significance test which resulted got t-statistic 9,024 and p-value 0,000, (4) to examine the influence of working satisfaction on Organizational Citizenship Behavior (OCB). This was proved in the coefficient significance test which resulted got t-statistic 1,247 and p-value 0,021, (5) to examine the influence of working satisfaction on organizational commitment. This was proved in the coefficient significance test which resulted got t-statistic 5,426 and p-value 0,000, (6) to examine the influence of organizational commitment on Organizational Citizenship Behavior (OCB). This was proved in the coefficient significance test which resulted got t-statistic 4,034 and p-value 0,000.Keywords: Leadership, Working Satisfaction, Organizational Commitment and Organizational Citizenship Behavior (OCB)